Patient factors associated with diabetes medication adherence at different health literacy levels: a cross-sectional study at a family medicine clinic. Issue 4 (18th May 2020) - Huang, Yen-Ming; Shiyanbola, Olayinka O.; Chan, Hsun-Yu; Smith, Paul D.
ABSTRACT: Background: Type 2 diabetes (T2D) incurs tremendous health costs associated with various complications due to poor diabetes control. Medication adherence, which is correlated with patients' health literacy, should be consistently practiced achieving optimal diabetes control. A deeper understanding of the specific communication and psychosocial factors related to medication-taking behaviors across different levels of health literacy among people with T2D will guide the development of effective interventions and strategies to enhance medication adherence. Objectives: This cross-sectional study aimed to identify salient patient factors associated with diabetes medication adherence across different levels of health literacy. Methods: A questionnaire was administered via a face-to-face approach with 205 participants at a family medicine clinic. Study participants were all above 20 years of age with T2D, were prescribed at least one oral diabetes medication, and understood English. The questionnaire assessed participants' health literacy, self-efficacy for medication use, beliefs in medicines, patient-provider communication, perceived barriers to medication adherence, and self-reported medication adherence. Separate analysis of covariance was used to compare the mean scores of patient factors related to medication adherence across people with different health literacy levels. Results: The mean age of participants was 61 years old, and the majority of the participants were female (57%), White (75%), and college educated (62%). Thirty-three percent of the participants had adequate health literacy, but only 43% of them reported high adherence to their diabetes medications. Analysis of covariance showed that having stronger self-efficacy (P < 0.001), lower concern beliefs about medication (P = 0.047), and fewer perceived barriers to medication-taking (P < 0.001), are necessary for better medication adherence. Conclusion: Findings suggest that practitioners should address concern beliefs among low-adherent patients with low health literacy, help improve self-efficacy, and address perceived barriers to medication adherence among all low-adherent patients to optimally support patients' diabetes care.